2022
DOI: 10.1155/2022/5578284
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Public Health, Environment, Human Psychology, Global Socioeconomy, and Education

Abstract: The end of the year 2019 was marked by the introduction of a third highly pathogenic coronavirus, after SARS-CoV (2003) and MERS-CoV (2012), in the human population which was officially declared a global pandemic by the World Health Organization (WHO) on March 11, 2020. Indeed, the pandemic of COVID-19 (Coronavirus Disease 19) has evolved at an unprecedented rate: after its emergence in Wuhan, the capital of the province of Hubei of the People's Republic of China, in December 2019, the total number of confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 87 publications
(94 reference statements)
0
45
0
Order By: Relevance
“…Lockdowns during the COVID-19 pandemic dramatically decreased the social and economic activity worldwide. 34 Several studies have reported a significant reduction in air pollution concentrations during lockdowns in most polluted cities, such as New York, Milan, Bangkok, Delhi, and Wuhan; [35][36][37] this reduction may be because of less motor vehicle traffic and suspended manufacturing. According to data provided by the Freeway Bureau, Ministry of Transportation and Communications of Taiwan, a decrease in motor vehicle traffic was noted during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…Lockdowns during the COVID-19 pandemic dramatically decreased the social and economic activity worldwide. 34 Several studies have reported a significant reduction in air pollution concentrations during lockdowns in most polluted cities, such as New York, Milan, Bangkok, Delhi, and Wuhan; [35][36][37] this reduction may be because of less motor vehicle traffic and suspended manufacturing. According to data provided by the Freeway Bureau, Ministry of Transportation and Communications of Taiwan, a decrease in motor vehicle traffic was noted during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, not to be underestimated are the indirect costs of the disease (i.e., within the profile of COPD/asthma patients) due to the loss of productivity and premature retirement of patients. The importance of these aspects is highlighted by the vast amount of literature dealing with the magnitude of resources needed to treat patients with these severe disorders, and with the public health measures taken by the world governments to face their impact on human psychology, the educational system, and the global economy [ 74 , 75 , 76 , 77 , 78 ]. How can proteomics alleviate these issues?…”
Section: Exploring the Role Of Biomarkersmentioning
confidence: 99%
“…In March 2020, Indonesia was shocked by the outbreak of Coronavirus Disease 2019 . The virus first appeared in Wuhan in December 2019 (Miyah et al, 2022). It is a contagious disease and attacks the human respiratory system.…”
Section: Introductionmentioning
confidence: 99%